Linux's challenge to Unix. - Cass, S. (IEEE spectrum)
Open-source software, widely seen as threatening to the most popular proprietary systems, may not be so threatening after all. The server market appears to be locked in a three-way battle of operating systems, with Microsoft Windows, proprietary Unix variants, and fast-growing Linux fighting it out. For Linux, most of that growth has come not from cutting into Microsoft territory, but from cannibalizing the market share of Unixes sold by the likes of IBM, Sun Microsystems, Silicon Graphics (SGI), and Hewlett-Packard. Rumors of the death of these proprietary Unixes, though, have been greatly exaggerated; they will live on for the next few years, and probably well beyond. Companies are sticking with them not because of their intrinsic merit, but for the sake of the end-user applications that run on the Unix platform, such as molecular modeling programs for pharmaceutical research.